Motor and sensory morbidity associated with the anterolateral thigh perforator free flap. (6th November 2017) - Noel, Christopher W.; Vosler, Peter S.; Hong, Michael; Orsini, Mario; Sultanov, Fayzullo; Lu, Zihang; Busato, Gian‐Marco; Enepekides, Danny; Higgins, Kevin
Abstract : Objective: To quantify changes in motor function, sensation, and lower extremity quality of life following anterior lateral thigh free flap (ALT) resection. Methods: This mixed methods study contained both a prospective cohort arm (n = 20) and retrospective cross‐sectional arm (n = 20). In both arms, patients underwent formal motor and sensation testing of the ipsilateral and contralateral thigh by sphygmomanometry and monofilament testing. In the prospective arm, data was collected preoperatively and at the 6‐month and 1‐year follow‐up visits. In the retrospective arm, consecutive patients with a minimum of 6‐month postoperative follow‐up were enrolled. Results: Postoperatively, 82% of participants endorsed some degree of numbness and tingling at the donor site. On monofilament testing, patients from the prospective arm showed decreased sensibility of the midthigh at both the 6‐ and 12‐month assessment ( P < 0.01). Two‐point discrimination scores were moderately correlated with the cross‐sectional surface area of the flap. Donor thighs demonstrated a similar peak isometric quadriceps contraction (retrospective [retro]: 47 ± 24 mmHg, prospective [pro]: 90 ± 36 mmHg) to the unoperated thighs (retro: 43 mmHg ± 22, pro: 69 ± 35.3 mmHg, P = 0.49). When stratified by perforator anatomy, no significant differences were noted. Subjective donor site morbidity measured with the lower extremity function scale demonstrated no statistically significant difference between the preoperative and 12‐month postoperative assessment. Conclusion: The ALT flap offers minimal donor site morbidity. Reduced sensibility of the ALT flap is a common complaint among patients. Quadriceps strength is not significantly affected by an ALT free flap harvest. Level of Evidence: 4. Laryngoscope, 128:1057–1061, 2018